“Afectación de derechos fundamentales en la jurisdicción de las rondas campesinas en Chota Cajamarca” - Edquén Campos, Máximo (2019)
ABSTRACT This research work aims to determine the causes of daily conflicts, existing between the judiciary and the peasant rounds. However, the Rounds have special jurisdiction granted by law, problems arise daily, including clashes between peasant rounds, the judiciary and law operators. Our goal is to propose a solution in order to avoid conflicts between two institutions: The peasant rounds recognized by law and the constitution and the judiciary, a state agency responsible for the administration of ordinary justice. Throughout our investigation we have established that the conflict of competences is generated because there is no legislation that delimits the competition of peasant rounds. Although the judiciary is seriously questioned because of the little procedural speed, as well as the lack of transparency in the administration of justice, it is also true that the peasant rounds in their eagerness to administer justice in the scope of their jurisdiction create discomfort to the judges who try to ignore customary law and customs and customs of the peasant rounds. More abundantly, the rounds resolve conflicts in different aspects, civil, criminal, family, etc. In many cases they exceed and generate problems with the same members of their community, resulting in frequent cases reported by kidnapping, coercion, usurpation of functions, etc. In this context, the present investigation consists in describing and explaining the formative process, the mechanisms and procedures used in the resolution of conflicts, the rural development activities promoted by the peasant rounds of Chota, within the framework of respect for human rights and organizational development; actions that in many cases generate controversy because the integrity of the investigated person is not guaranteed, that is, in the inquiries within the hovering organization a due process is not respected, the procedures and inquiries are consistent with their uses and customs, it is more Our Magna Carta guarantees the due process, with the presumption of innocence, the pro-probation and the defense of the accused, rights that are not exercised within the organization hovering. With the healthy purpose of taking legal gaps and compromising a close relationship between peasant rounds and the judiciary, I propose a rule that delimits both territorial competence and subject matter competence for peasant rounds, at the same time a rights education program is suggested human and organizational development for the peasant rounds to improve the performance of ronderil in the resolution of conflicts, in coordination with the judiciary and with respect to due process, in order to avoid criminal proceedings for usurpation and other crimes attributed to the ronderos. Knowing the efficiency in the administration of justice of the peasant rounds, within the scope of their jurisdiction I propose at the same time, the modification of the criminal procedural code in relation to the preliminary investigation, in whose inquiries the hobbyists should participate and be considered as evidence the acts and clarifications that they make in the rural communities are valid. It is good to note that in order to formalize this work, the investigator has used interviews with the ronderos, interviews with judges, prosecutors and other law operators working in chota-Cajamarca.